Decapping is preceded by 3' uridylation in a novel pathway of bulk mRNA turnover. - Rissland, O; Norbury, C (2009)
Both end structures of eukaryotic mRNAs, namely the 5' cap and 3' poly(A) tail, are necessary for transcript stability, and loss of either is sufficient to stimulate decay. mRNA turnover is classically thought to be initiated by deadenylation, as has been particularly well described in Saccharomyces cerevisiae. Here we describe two additional, parallel decay pathways in the fission yeast Schizosaccharomyces pombe. First, in fission yeast mRNA decapping is frequently independent of deadenylation. Second, Cid1-dependent uridylation of polyadenylated mRNAs, such as act1, hcn1 and urg1, seems to stimulate decapping as part of a novel mRNA turnover pathway. Accordingly, urg1 mRNA is stabilized in cid1Delta cells. Uridylation and deadenylation act redundantly to stimulate decapping, and our data suggest that uridylation-dependent decapping is mediated by the Lsm1-7 complex. As human cells contain Cid1 orthologs, uridylation may form the basis of a widespread, conserved mechanism of mRNA decay.